Examining the Relationship Between Entrepreneurship, Marketing Capability, Innovation, and Business Strategy on Sustainable Firm Performance: A Case Study of SMEs in Thailand's Special Economic Zone - Yaemsaeng, Anu (Digital Repository of Theses, 2024)
This research investigates the multifaceted interplay between entrepreneurship, marketing capabilities, innovation, business strategy, and firm performance within the context of small and medium-sized enterprises (SMEs) in the Special Economic Zone (SEZ) of Thailand. The study aims to determine the effect of these core components on the sustainable performance and competitive advantage of SMEs. The primary objective is to analyse how entrepreneurship and marketing capabilities drive innovation and business strategy, ultimately influencing sustainable firm performance. The research focuses on understanding these dynamics within the Thai SEZ context to provide actionable insights for policy makers and academic researchers. A quantitative research methodology was employed, involving a survey of 327 SMEs in the SEZ. The data collected were subjected to various statistical analyses, including normal distribution tests, confirmatory factor analysis, and structural equation modelling, to validate the proposed conceptual framework and test the hypotheses. The findings reveal that entrepreneurship and marketing capabilities significantly impact innovation, which in turn influences business strategy. The results underscore that a well-defined business strategy is critical for achieving sustainable firm performance. Furthermore, the study confirms that innovation acts as a mediator between entrepreneurship, marketing capabilities, and business strategy, facilitating the translation of entrepreneurial and marketing efforts into strategic actions that enhance firm performance. The research concludes that fostering entrepreneurship and enhancing marketing capabilities are vital for SMEs aiming to innovate and develop robust business strategies. This study provides empirical evidence supporting the strategic integration of these elements to achieve sustainable performance in competitive markets. The insights derived from this research can inform policy development and guide future academic inquiries into the dynamics of SME performance in similar economic zones.